Analisis Implementasi Akad Ju’alah dalam Program Affiliasi Digital Studi Kompratif Shopee Affiliate dan Tiktok Affiliate - Silviana Rohimah; Nurul Huda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted with the aim of analyzing the implementation of the ju'alah contract in digital affiliate programs, namely Shopee Affiliate and Tiktok Affiliate, and comparing the mechanisms of both in the context of sharia economic law. The ju'alah contract is a form of muamalah contract based on services, where someone offers compensation (ju'l) to another party for certain work that has been agreed upon in advance. This study examines both affiliate programs in terms of fairness, transparency, and sustainability, which are the main principles in sharia economics. This study uses a qualitative research method with descriptive analysis with a library research approach to identify how the ju'alah contract is applied in digital affiliate marketing practices, the challenges faced, and opportunities that can be utilized to increase the effectiveness of its implementation. The results of the study show that although there are similarities in the basic principles of the ju'alah contract between Shopee Affiliate and Tiktok Affiliate, there are differences in the implementation and payment mechanisms that need to be considered regarding sharia principles, such as clarity of rewards, transparency, and fairness. This study can provide recommendations for improvements in terms of payment transparency according to sharia principles on both platforms to ensure compliance with deeper sharia economic values.